Green extraction of nutritional and antioxidant valuable compounds from wine by-products - Barba, Francisco J.; Gómez, Belén; Denoya, Gabriela Inés; Brnčić, Mladen; Brnčić, Suzana Rimac; Lorenzo, José M.; Moreno, Andrés (Taylor & Francis, 2020)
The world wine-growing area in 2017 stands at 7.5 million hectares, with Spain having the largest number (967,000 ha), around 13% of the world surface, ranking ahead of countries, such as China (870,000 ha) and France (786,000 ha) (OIV [The International rganization of Vine and Wine], 2019). In terms of world’s wine production, Italy is the leading producer (48.5 million hectoliters), ollowed by France (46.4 million hectoliters) and Spain (40.9 million hectoliters) (OIV, 2019). During the wine production process, a large number of wastes and by-products are generated (Figure 8.1), having a large number of valuable compounds with a high nutritional value and biological properties (e.g., proteins and bioactive compounds). Among the bioactive compounds present in the vinification products, polyphenols represent one of the most important groups of atural products associated with healthy benefits (Haminiuk et al., 2012). In the last two decades, there has been a growing interest in these compounds by the scientific community due to their numerous beneficial properties, many of them associated with their ntioxidant capacity. Up to now, the nature of all these compounds and the mechanism of action are not completely known, although it has been shown that, depending on the chemical structure, they have different antioxidant properties. Then, their antioxidant activity not only depends on the quantity but also on the type of phenolic compound that is obtained. For this reason, the selective extraction of these compounds acquires a relevant interest. Particularly, some phenolic compounds were associated with antiallergenic, anti- nflammatory, antimicrobial, antioxidant, antithrombotic, and cardioprotective properties (Beres et al., 2017). One of the main objectives in Europe is the elimination of waste in a sustainable way. Traditionally, many of the residues from the agri-food industry have been iscarded without further consideration, without taking into account that they could represent a valuable source of compounds with a high nutritional value. However, in recent decades, there has been a growing interest from both the food industry and the scientific ommunity to add value to these residues. One of the solutions is the extraction of compounds that can be used in different applications, such as pharmaceutical, food, and so on, as food additives, or nutraceuticals, among others. For instance, this year, BacaBocanegra et al. (2019) contributed to the global idea of waste reduction and by-product valorization, studying the potential use of wine by-products as a source of copigments for improving the quality of wines. Conventional solid–liquid extraction (SLE) has been the main way to extract these compounds. However, in many cases, this involves the use of solvents that can be toxic and the use of temperatures above 60 ºC, with the subsequent degradation of thermolabile compounds. Thus, the use of new green technologies that can partially or totally replace conventional methodologies is being investigated to reduce solvent consumption, as well as to reduce the temperature and the treatment time. The purpose is to achieve more efficient and sustainable processes from the economic and environmental point of view. The application of conventional and innovative extraction processes (Figure 8.2) on the different wine industry wastes and by-products for obtaining valuable products is discussed in the different sections of this chapter.